Rapid automated identification of gram-negative bacilli from blood cultures with the AutoMicrobic system. - Schifman, R B (1982)
Automated identification of gram-negative bacilli directly from blood culture bottles by using the AutoMicrobic System (AMS) was evaluated with a modified procedure for the AMS Enterobacteriaceae-plus nonfermenter identification card. A total of 150 strains were tested (44 clinical and 106 seeded) and compared with a conventional identification procedure. These strains included 107 Enterobacteriaceae and 43 oxidase-positive or glucose-nonfermenting, or both, organisms. AMS identifications on one of these strains were not interpretable owing to equal probability AMS identification values. Of the remaining 149 strains, 138 (92.6%) were correctly identified within 8 to 13 h of the first reading. Of 69 identifications analyzed after 6 h of incubation, 91% were correct. This procedure was found to be rapid, convenient, and nonlabor intensive and is recommended for presumptive identification of gram-negative bacilli in blood cultures.